2002
DOI: 10.1080/00207390210130921
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related differences on open and closed assessment tasks

Abstract: The use of short assessment tasks can provide valuable information about undergraduates' knowledge and understanding. However, it is known that there are gender-related di erences in performance on certain types of objective tests, both among school pupils and university undergraduates. This article focuses on undergraduate learning, using a mixture of tasks presented in either an open or closed form. Although the success rate in performing the given tasks seems to depend on the degree of openendedness inheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Second, it may be that these differences in performance result from the different topics assessed in MC examinations rather than from gender differences per se. In support of this argument, the MC examination reported by Hartley et al (2007) assessed students' knowledge of neuropsychology, whereas the MC examination reported by Anderson (2002) assessed constructs aligned with mathematical ability.…”
Section: Multiple-choice Examinations In Psychologymentioning
confidence: 80%
See 3 more Smart Citations
“…Second, it may be that these differences in performance result from the different topics assessed in MC examinations rather than from gender differences per se. In support of this argument, the MC examination reported by Hartley et al (2007) assessed students' knowledge of neuropsychology, whereas the MC examination reported by Anderson (2002) assessed constructs aligned with mathematical ability.…”
Section: Multiple-choice Examinations In Psychologymentioning
confidence: 80%
“…First, gender differences may emerge because, when there is correction for guessing, males typically leave fewer questions unanswered and this may serve to increase their scores (Anderson, 2002;Ben-Shakhar & Sinai, 1991;Von Schrader & Ansley, 2006). Second, it may be that these differences in performance result from the different topics assessed in MC examinations rather than from gender differences per se.…”
Section: Multiple-choice Examinations In Psychologymentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages of the TFA format are that large numbers of examinees can be tested with relatively few resources, that marking is objective, that large areas of knowledge as well as specialist, in depth topics can be covered, that poor non-discriminatory questions can easily be identified and that large question banks are available. Nevertheless it has been found that there were significant gender effects when true/false questions were used in maths exams (Anderson 1989 as cited in [ 14 ]) and these differences were attributed to a female tendency to avoid risk-taking (Forgasz 1991 as cited in [ 14 ]). In older mathematics students the female superiority was restricted to specific types of mathematical knowledge [ 15 ].…”
Section: Introductionmentioning
confidence: 99%